Rozwój energetyki wiatrowej w regionie Azji i Pacyfiku - Pultowicz, Alicja (Wind Power Development in the Asia-Pacific Region, 2008)
The aim of this article is to analyze the development of wind power in the Asia-Pacific region. Most of the countries presented in the paper are the largest economies in the world. It is believed that the rapid economic growth will contribute to rising energy demand. The crucial drivers forcing countries to rapid renewable sources development are very few fossil fuel resources and necessity to import them. Additionally, with rapid economic growth they, produce large quantities of carbon dioxide and have very bad impact on the environment. What could improve the situation is the investment in renewable energy sources especially in the wind energy sector presented in the paper. It delivers energy security benefits of avoided fuel cost, is environmental friendly source of energy and has no long term fuel price risk, avoids the supply risk and dependence on other countries. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 190-201